Penonjolan Isu Media Arus Perdana, Media Alternatif dan Media Kerajaan di Twitter - Jamali Bujang, Sanawi; Normah, Mustaffa; Shahrul Nazmi, Sannusi (Department of Media and Communication Studies, Faculty of Arts and Social Sciences, University of Malaya, Malaysia, 2022)
The change of government that took place after the GE 14 demanded a review to be carried out on the pattern of agenda setting among the news media in this country, especially on social media. Therefore, this study examines how the mainstream media, alternative media and government media set their issue’s salience agenda on Twitter during the pre and post GE 14. A total of 7,533 tweets from six media organisations namely Berita Harian, The Star, Malaysiakini, Free Malaysia Today, BERNAMA and RTM were downloaded and analysed. A content analysis, bivariate correlation analysis and time-lagged analysis were conducted to identify the hierarchical pattern of issue’s salience and the causal relationship between issue’s salience agendas between these media. From the analysis, it was found that the mainstream media, the alternative media and the government media have a different inclinations in setting up their most important issue on Twitter during the pre and post GE 14. Mainstream media were found to place sports issues as the most important issue on their agenda on Twitter, while for alternative and government media, political issues and issues of national administration and governance were their top priorities. Meanwhile, the transition of the government post GE 14 also has an impact on the causal relationship between agendas involving the mainstream media, the alternative media and the government media on Twitter. For instance, during the pre GE 14 period, the agenda of the mainstream media did not have a significant relationship with the agenda of the government media. However during the post GE 14 period, the agenda of the two media was found to have a significant relationship. In the context of the causal relationship, the two media did not have a mutual influence on each other during the pre GE 14 period, but this situation changed after the GE 14. As for the alternative media, its relationship with the government media also changed after GE 14 in which its agenda no longer influences the government’s media agenda and vice versa. During the pre GE 14 period, the two media were found to have mutually influenced each other in their agenda on Twitter.